An effect comparison of alendronate and teriparatide in patients with glucocorticoid-induced osteoporosis: A protocol for systematic review and meta-analysis. Issue 48 (2nd December 2022) - Liang, Na; Zhang, Shuang; Wang, Shuang; Ma, Juan
Abstract : Background: Glucocorticoid-induced osteoporosis is the most common secondary cause of osteoporosis and the resulting fractures cause significant morbidity. Oral bisphosphonates are currently regarded as first line options on the grounds of their low cost. However, teriparatide has been shown to be superior in its effects on bone mineral density and vertebral fracture risk in glucocorticoid-treated individuals with osteoporosis. We conducted a protocol for systematic review and meta-analysis to assess the effectiveness of alendronate and teriparatide in patients with glucocorticoid-induced osteoporosis. Methods: The study protocol has been registered on international prospective register of systematic review (PROSPERO registration number: CRD42022371561). The procedure of this protocol will be conducted according to the Preferred Reporting Item for Systematic Review and Meta-analysis Protocols guidance. PubMed, EMBASE, MEDLINE, the Cochrane Library, Chinese National Knowledge Infrastructure, Chinese Biomedical Literature Database, Wanfang Database, ClinicalTrials.gov trials registry, and Chinese Clinical Trial Registry will be searched from January 1980 to November 2022. Two authors will assess methodological quality of included studies separately by the Cochrane collaboration's risk of bias tool. We will apply RevMan 5.4 software for statistical analysis. Results: This study will provide a high-quality comprehensive evaluation of the efficacy and safety of alendronate and teriparatide for treating patients with glucocorticoid-induced osteoporosis. Conclusion: The conclusion of our systematic review will provide evidence to judge whether teriparatide is an effective intervention for patients with glucocorticoid-induced osteoporosis.